1962
DOI: 10.1037/h0083222
|View full text |Cite
|
Sign up to set email alerts
|

Blocking in serial simple reaction tasks.

Abstract: A series of visual or auditory stimuli were presented at different intervals and reaction times were recorded. Occasional blocks (latencies 3.29 times greater than the SD) occurred for all Ss. There was no evidence of a correlation between blocking and fatigue, nor was periodicity revealed. Too little is known about the conditions which generate blocks to warrant the formulation of a theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1963
1963
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Laming (1968, pp. 117-119) was one of the first to report autocorrelations in RTs (see also Foley & Humphries, 1962). In order to account for data from five experiments showing quickly decaying autocorrelations that remained significantly different from zero up to about lag 6 and that were unrelated to the experimental variables, Laming (1968) proposed that the level of attention paid to the experiment on trial i, A i , is given by A i ϭ A ϩ x i , where A is a constant.…”
Section: Previous Accounts Of Serial Dependence In Human Cognition: Fmentioning
confidence: 99%
“…Laming (1968, pp. 117-119) was one of the first to report autocorrelations in RTs (see also Foley & Humphries, 1962). In order to account for data from five experiments showing quickly decaying autocorrelations that remained significantly different from zero up to about lag 6 and that were unrelated to the experimental variables, Laming (1968) proposed that the level of attention paid to the experiment on trial i, A i , is given by A i ϭ A ϩ x i , where A is a constant.…”
Section: Previous Accounts Of Serial Dependence In Human Cognition: Fmentioning
confidence: 99%
“…In this experiment a RT > .350 sec. was a block as defined by Foley and Humphries (1962). In such cases another RT trial was presented to the subject.…”
Section: Resultsmentioning
confidence: 99%
“…Using simple visual and auditory RT tasks, Foley and Humphries (75) found that blocks occurred uniformly throughout 14-to 60-mih test periods; but no evidence was found that the occurrence of a block dissipated fatigue buildup, for no gradual increase occurred in RT up to a block and no abrupt decrease in RT after the block. However, since RT did not increase from the beginning to end of the trials, errors were not measured and no subjective fatigue data were collected, so these researchers (75) had no evidence of any fatigue during this type of task.…”
Section: Response Blocking As An Indicator Of Fatiguementioning
confidence: 99%
“…However, since RT did not increase from the beginning to end of the trials, errors were not measured and no subjective fatigue data were collected, so these researchers (75) had no evidence of any fatigue during this type of task. In contrast, Bertelson and Joffe (28)--using a fourchoice serial RT task lasting only 30 min--found that RT rose sharply during the four or five responses preceding a block, and fell abruptly following a block, thus supporting Bills' hypothesis that the function of blocks is to dissipate fatigue buildup.…”
Section: Response Blocking As An Indicator Of Fatiguementioning
confidence: 99%